Product Innovation Transformation and Process Efficiency through the Strategic Role of Business Information Systems in Technology Startups in the Digital Era - Prakosos, Riyan Dwi Yulian; Wakhidah, Esti Nur; Sinatria, Ridhwan; Maulida, Juwita Dien; Makarim, Nabil (PT. LITERASI SAINS NUSANTARA, 2025)
The digital era has driven technology startups to adopt business information systems to enhance product innovation and operational process efficiency. This study aims to analyze the strategic role of business information systems in driving innovation transformation and optimizing business processes in technology startups. Using a literature review method with a qualitative approach and descriptive analysis, this study examines 17 articles obtained from Google Scholar from the 2019–2025 period. The findings indicate that the implementation of data analytics, artificial intelligence, and cloud computing-based business information systems enables startups to develop more innovative products and improve supply chain efficiency as well as internal management. Case studies of Gojek, Tokopedia, Ruangguru, and Qasir confirm that business information systems assist startups in data-driven decision-making, enhancing customer experience, and optimizing resources. However, challenges such as limited resources and organizational readiness remain obstacles to the optimal implementation of business information systems. This study provides implications for startups, investors, and policymakers in designing more effective technology adoption strategies to support the growth of the startup industry.